Spectroscopic Study of Synthesized Copper Nanoparticles by Chemical Reduction Method - N. Padole, Nandkishor; Majgavali, Nilesh V.; Meshram, Monali A.; Padole, Nitin N. (Asian Journal of Pharmaceutical Research and Development, 2024)
Well-dispersed and uniform-size preparation of Copper nanoparticles and its X-ray diffraction studies are reported in this paper. A simple and cheapest chemical reduction method with copper sulfate pentahydrate as a main precursor is used for the synthesis of Copper nanoparticles. A wide range of experimental conditions has been adopted in this process and its X-Ray diffraction characterizations have been studied. UV-visible spectroscopic analysis showed the maximum absorption at 295 nm. Transmission electron microscopy reveals the spherical morphology of the synthesized particles. The results confirm copper nanopowder with an average particle size in the range of 30-60 nm.